Use of Probiotic Bacteria and Bacteriocins as an Alternative to Antibiotics in Aquaculture - Pereira, Wellison Amorim (2022)
In addition to their use in human medicine, antimicrobials are also used in food animals and aquaculture, and their use can be categorized as therapeutic against bacterial infections. The use of antimicrobials in aquaculture may involve a broad environmental application that affects a wide variety of bacteria, promoting the spread of bacterial resistance genes. Probiotics and bacteriocins, antimicrobial peptides produced by some types of lactic acid bacteria (LAB), have been successfully tested in aquatic animals as alternatives to control bacterial infections. Supplementation might have beneficial impacts on the intestinal microbiota, immune response, development, and/or weight gain, without the issues associated with antibiotic use. Thus, probiotics and bacteriocins represent feasible alternatives to antibiotics. Here, we provide an update with respect to the relevance of aquaculture in the animal protein production sector, as well as the present and future challenges generated by outbreaks and antimicrobial resistance, while highlighting the potential role of probiotics and bacteriocins to address these challenges. In addition, we conducted data analysis using a simple linear regression model to determine whether a linear relationship exists between probiotic dose added to feed and three variables of interest selected, including specific growth rate, feed conversion ratio, and lysozyme activity.